The innovators : the engineering pioneers who made American modern - Billington, David P. (New York : John Wiley and Sons, 1996)
This book is about: Iron, Steam, and Early Industry, 1776-1855; Crossing the continent, 1830-1883;...
Keywords: Engineering; Technological innovations; Engineering -- United States -- History; Technological innovations -- United States -- History; Engineers -- United States